Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's evaluate each of the given expressions step-by-step to determine which one is equivalent to [tex]\(\left(\frac{1}{16}\right)\)[/tex].
### Option 1: [tex]\(-(16)^4\)[/tex]
First, we calculate [tex]\(16^4\)[/tex]:
[tex]\[ 16^4 = 65536 \][/tex]
Next, we apply the negative sign:
[tex]\[ -(65536) = -65536 \][/tex]
So, [tex]\(-(16)^4 = -65536\)[/tex].
### Option 2: [tex]\(16^4\)[/tex]
We already calculated this in the previous step:
[tex]\[ 16^4 = 65536 \][/tex]
### Option 3: [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]
This can be rewritten using exponent notation:
[tex]\[ \sqrt[4]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{4}} \][/tex]
Evaluating this:
[tex]\[ \left(\frac{1}{16}\right)^{\frac{1}{4}} = \left(16^{-1}\right)^{\frac{1}{4}} = 16^{-\frac{1}{4}} \][/tex]
[tex]\[ 16^{-\frac{1}{4}} = \left(2^4\right)^{-\frac{1}{4}} = 2^{-1} = \frac{1}{2} \][/tex]
So, [tex]\(\sqrt[4]{\frac{1}{16}} = 0.5\)[/tex].
### Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]
First, we calculate [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
[tex]\[ \left(\frac{1}{16}\right)^{-4} = \left(16^{-1}\right)^{-4} = 16^{4} = 65536 \][/tex]
Next, we apply the negative sign:
[tex]\[ -65536 \][/tex]
So, [tex]\(-\left(\frac{1}{16}\right)^{-4} = -65536\)[/tex].
### Comparing Results
The value we seek is [tex]\(\frac{1}{16}\)[/tex].
[tex]\[ \frac{1}{16} = 0.0625 \][/tex]
Comparing all computed values:
- Option 1: [tex]\(-65536\)[/tex]
- Option 2: [tex]\(65536\)[/tex]
- Option 3: [tex]\(0.5\)[/tex]
- Option 4: [tex]\(-65536\)[/tex]
None of these values match [tex]\(\left(\frac{1}{16}\right) = 0.0625\)[/tex].
Therefore, none of the given expressions are equivalent to [tex]\(\left(\frac{1}{16}\right)\)[/tex].
### Option 1: [tex]\(-(16)^4\)[/tex]
First, we calculate [tex]\(16^4\)[/tex]:
[tex]\[ 16^4 = 65536 \][/tex]
Next, we apply the negative sign:
[tex]\[ -(65536) = -65536 \][/tex]
So, [tex]\(-(16)^4 = -65536\)[/tex].
### Option 2: [tex]\(16^4\)[/tex]
We already calculated this in the previous step:
[tex]\[ 16^4 = 65536 \][/tex]
### Option 3: [tex]\(\sqrt[4]{\frac{1}{16}}\)[/tex]
This can be rewritten using exponent notation:
[tex]\[ \sqrt[4]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{4}} \][/tex]
Evaluating this:
[tex]\[ \left(\frac{1}{16}\right)^{\frac{1}{4}} = \left(16^{-1}\right)^{\frac{1}{4}} = 16^{-\frac{1}{4}} \][/tex]
[tex]\[ 16^{-\frac{1}{4}} = \left(2^4\right)^{-\frac{1}{4}} = 2^{-1} = \frac{1}{2} \][/tex]
So, [tex]\(\sqrt[4]{\frac{1}{16}} = 0.5\)[/tex].
### Option 4: [tex]\(-\left(\frac{1}{16}\right)^{-4}\)[/tex]
First, we calculate [tex]\(\left(\frac{1}{16}\right)^{-4}\)[/tex]:
[tex]\[ \left(\frac{1}{16}\right)^{-4} = \left(16^{-1}\right)^{-4} = 16^{4} = 65536 \][/tex]
Next, we apply the negative sign:
[tex]\[ -65536 \][/tex]
So, [tex]\(-\left(\frac{1}{16}\right)^{-4} = -65536\)[/tex].
### Comparing Results
The value we seek is [tex]\(\frac{1}{16}\)[/tex].
[tex]\[ \frac{1}{16} = 0.0625 \][/tex]
Comparing all computed values:
- Option 1: [tex]\(-65536\)[/tex]
- Option 2: [tex]\(65536\)[/tex]
- Option 3: [tex]\(0.5\)[/tex]
- Option 4: [tex]\(-65536\)[/tex]
None of these values match [tex]\(\left(\frac{1}{16}\right) = 0.0625\)[/tex].
Therefore, none of the given expressions are equivalent to [tex]\(\left(\frac{1}{16}\right)\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.